2013
DOI: 10.1016/j.tox.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards the validation of a lung tumorigenesis model with mainstream cigarette smoke inhalation using the A/J mouse

Abstract: A generally accepted and validated laboratory model for smoking-associated pulmonary tumorigenesis would be useful for both basic and applied research applications, such as the development of early diagnostic endpoints or the evaluation of modified risk tobacco products, respectively. The A/J mouse is susceptible for developing both spontaneous and induced lung adenomas and adenocarcinomas, and increased lung tumor multiplicities were also observed in previous cigarette smoke inhalation studies. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…It also continues to be useful for evaluation of chemointerventive agents of lung neoplasia [24,26,27]. This strain is susceptible to both chemically-induced and spontaneous lung adenomas compared to the resistant B6 mouse [23].…”
Section: Discussionmentioning
confidence: 99%
“…It also continues to be useful for evaluation of chemointerventive agents of lung neoplasia [24,26,27]. This strain is susceptible to both chemically-induced and spontaneous lung adenomas compared to the resistant B6 mouse [23].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was a sub-study of an A/J mouse validation study, and its design has been previously described in detail (Stinn et al , 2013a ; Stinn et al , 2013b ). Briefly, male A/J mice aged between 8 and 12 weeks received whole-body exposure to MS at concentrations of 75, 150, and 300 mg/m 3 of total particulate matter (TPM) (animal groups MS-75, MS-150, and MS-300, respectively) from the 3R4F reference cigarette (University of Kentucky, Lexington, KY, USA) for 6 h/day and 5 days/week for 18 months.…”
Section: Methodsmentioning
confidence: 99%
“…Histopathologic evaluation was conducted on mice exposed to air (sham control, N=27) and to MS of the 3R4F cigarette smoke, (N=33, 37, and 34 mice of the MS-75, MS-150 and MS-300 groups, respectively) by a certified pathologist, who was blinded to the individual treatment of the animals, as reported previously (Stinn et al , 2013a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This drawback depends on the general difficulty to test complex mixtures rather than individual compounds in experimental settings as well as on various problems inherent to exposure by inhalation of rodents, such as the different anatomy of the upper respiratory tract and the fact that rodents are obligate nose-only breathers. As a consequence, most carcinogenicity studies in a variety of animal species showed that inhaled CS is either negative or just weakly positive [710]. Our attempts to use transgenic mice, such as p53 mutant mice [11], failed to enhance the carcinogenic response.…”
Section: Carcinogenicity Of Cigarette Smoke In Humans and Animal Modelsmentioning
confidence: 99%